The use of solid phase microextraction technique for the extraction of trihalomethanes in drinking water - Md. Pauzi Abdullah,; Aiman M. Bobaker, (Universiti Kebangsaan Malaysia, 1999)
Solid phase micro-extraction technique is a fast, sensitive, inexpensive, portable and solvent free method for extracting organic compounds from aqueous samples. This technique involves exposing a fused silica fibre that has been coated with a stationary phase to an aqueous solution containing organic contaminants. The analytes partition into the stationary phase until an equilibrium has been reached, after which the fibre is removed from the solution and the analytes are thermally desorbed into the injector of a gas chromatograph. Optimization work were carried out for the time of absorption and desorption, and the equilibrium temperatures for the extraction of trihalomethanes in drinking water samples. Almost 100% recovery was achieved within three minutes of equilibration between 25 to 30°C with desorption time of two minutes. The samples of drinking water supplies were analyzed against calibrated standard solutions in deionized water. With 20.0 ml water sample, the method's detection limit MDL of 0.01 ppb was achieved for CHCl3 and CHBrCI2. For CHBr2Cl and CHBr3 the MDL were 0.04 and 0.06 ppb, respectively.